Control and Transfer of Chirality Within Well-Defined Tripodal Supramolecular Cages - Qiu, Gege; Nava, Paola; Colomban, Cédric; Martinez, Alexandre (Frontiers in Chemistry, 2020)
The development of new strategies to turn achiral artificial hosts into highly desirable chiral receptors is a crucial challenge in order to advance the fields of asymmetric transformations and enantioselective sensing. Over the past few years, C3 symmetrical cages have emerged as interesting class of supramolecular hosts that have been reported as efficient scaffolds for chirality dynamics (such as generation, control, and transfer). On this basis, this mini review, which summarizes the existing examples of chirality control and propagation in tripodal supramolecular cages, aims at discussing the benefits and perspectives of this approach.